Carcinoma and DNA aneuploidy in Crohn's colitis–a histological and flow cytometric study. Issue 8 (August 1991) - Löfberg, R; Broström, O; Karlén, P; Ost, A; Tribukait, B
Abstract : Twenty four patients with longstanding colonic Crohn's disease were examined prospectively with colonoscopy and multiple biopsy sampling in order to detect histological dysplasia or abnormal aneuploid DNA content, or both. Biopsy specimens were taken from 10 predetermined locations in the colon and rectum. No patient had definite dysplasia but three displayed DNA aneuploidy (12.5%), and one of these subsequently developed a carcinoma (Dukes' C at operation) in the ascending colon. No concomitant dysplasia was detected but the carcinoma as well as other parts of the mucosa were DNA aneuploid. It is concluded that dysplasia is rare in patients with Crohn's colitis, but findings of DNA aneuploidy warrant vigilance in follow up as this may indicate impending carcinoma. Further prospective studies are needed before the predictive value of DNA aneuploidy can be determined and before general recommendations of colonoscopic surveillance, as in longstanding ulcerative colitis, can be made.